ANALISIS DAMPAK BUDAYA ORGANISASI, KUALITAS SUMBER DAYA MANUSIA, KUALIFIKASI KARYAWAN TERHADAP DISTRIBUSI TENAGA KERJA (Studi Kasus pada Puskesmas Wonoayu Kab. Sidoarjo) (JEB17 : Jurnal Ekonomi dan Bisnis, 2025)
Abstract This research was conducted in order to analyse the impact of organisational culture, human resource quality, and employee qualifications on workforce distribution among employees at the Wonoayu Health Centre. The approach used in this research is a quantitative approach. The research population used is all employees of the Wonoayu Health Centre with a total of 90 respondents through saturated sampling techniques which make all populations a sample in this research. The data source used in this analysis is primary data where the collection is done directly from Wonoayu Health Centre employees by distributing questionnaires. The data source used in this analysis is data which is taken directly from employees where in this research is the Wonoayu Health Centre Employees by distributing questionnaires. The results obtained in this research show that the Organisational Culture variable has a significant effect on Manpower Distribution, the Human Resource Quality variable has a significant effect on Manpower Distribution, the Employee Qualification variable has a significant effect on Manpower Distribution, and the organisational culture variable (X1), human resource quality (X2), and employee qualifications (X3) have a positive and significant effect on manpower distribution (Y). Keywords: Organisational Culture, Human Resource Quality, Employee Qualifications, Labour Distribution